2014
DOI: 10.1017/s0373463314000204
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Calculate the Vertical Protection Level in A-RAIM

Abstract: Four methods to calculate the Vertical Protection Level (VPL) can be used in Advanced Receiver Autonomous Integrity Monitoring (A-RAIM), among which the ideal method is the strictest one. To obtain the ideal VPL satisfying the exact required integrity risk, the worst case bias with the maximum integrity risk is searched for. This investigation has found that the correct worst case highly depends on the choice of the input VPL. To gain the correct result, the computation becomes complex and the accuracy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Determining the worst-case f i is achieved using a line-search process, also implemented in Lee (1995), Milner and Ochieng (2010) and Jiang and Wang (2014). The line search can be avoided using the alternative approach given in Section 3.…”
Section: N T E G R I T Y R I S K M I N I M I S At I O N I N R a I Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the worst-case f i is achieved using a line-search process, also implemented in Lee (1995), Milner and Ochieng (2010) and Jiang and Wang (2014). The line search can be avoided using the alternative approach given in Section 3.…”
Section: N T E G R I T Y R I S K M I N I M I S At I O N I N R a I Mmentioning
confidence: 99%
“…To simplify the calculations in the upcoming derivation, a tight integrity risk bound is given by: where, as defined in Part 1, P Hi is the prior probability of occurrence of hypothesis H i (i.e., fault on measurement subset i ), and f i is the single-Satellite Vehicle (SV) fault magnitude under H i . Determining the worst-case f i is achieved using a line-search process, also implemented in Lee (1995), Milner and Ochieng (2010) and Jiang and Wang (2014). The line search can be avoided using the alternative approach given in Section 3.…”
Section: Non-least-squares Estimator Design To Minimise Integrity Riskmentioning
confidence: 99%
“…Multiple implementations of SS and χ 2 RAIM have been derived, for example, regarding the treatment of the worst-case fault magnitude as explained in Lee (1995), Milner and Ochieng (2010) and Jiang and Wang (2014). In order to establish fair grounds for analysis, the approach pursued in this paper is based on a common, tight integrity risk bound defined in Section 2.…”
Section: Introduction Receiver Autonomous Integrity Monitoring (Raim)mentioning
confidence: 99%
“…The worst-case fault magnitude f i , which maximizes the integrity risk given H i , is found using a straightforward line search algorithm (e.g., used in Lee (1995), Milner and Ochieng (2010) and Jiang and Wang (2014)). For the fault-free case (i = 0), the following notation is used: f 0 = 0.…”
Section: Introduction Receiver Autonomous Integrity Monitoring (Raim)mentioning
confidence: 99%
“…But it is observed that the iterative method is not able to control the accuracy of the results with uncertainty caused by the number of steps, and is computationally heavy with two search loops. Therefore, a new approach is proposed here to improve these two performance criteria based on the method in Jiang and Wang (2014) for the Vertical Protection Level (VPL) computation. A new iterative method with one search loop is designed with results showing that it has higher computational efficiency, but the accuracy of the results is still uncertain.…”
mentioning
confidence: 99%